Orthostatic Resiliency During Successive Hypoxic, Hypoxic Orthostatic Challenge: Successful vs. Unsuccessful Cardiovascular and Oxygenation Strategies - Nordine, Michael; Treskatsch, Sascha; Habazettl, Helmut; Gunga, Hanns-Christian; Brauns, Katharins; Dosel, Petr; Petricek, Jan; Opatz, Oliver (Frontiers in Physiology, 2021)
Introduction: Successive hypoxic-hypoxic orthostatic challenges (SHHOC) occur in the aerospace environment, and the ability to remain orthostatically resilient (OR) relies upon physiological counter-responses. Counter-responses adjusting for hypoxia may conflict with orthostatic responses, and a misorchestration leads to orthostatic intolerance (OI). The goal of this study was to pinpoint factors associated with OR during simulated SHHOC. Methods: 31 men underwent a SHHOC consisting of baseline (P0), normobaric hypoxia (Fi02=12%, P1), and max 60 seconds of hypoxic lower body negative pressure (LBNP, P2). Anthropometric, cardiovascular, central/peripheral tissue oxygenation parameters were recorded. OI was defined as hemodynamic collapse during SHHOC. Comparison of anthropometric, cardiovascular, and oxygenation parameters between OR and OI was performed via students T-test. Within groups, a repeated measures ANOVA test with Holm-Sidak post-hoc test was performed. Performance diagnostics were performed for significant factors (sensitivity, specificity, positive predictive value PPV, and odd’s ratio OR). Results: 9/31 were OR, and 22/31 were OI. OR had greater body mass index (BMI), weight, longer R-R Interval (RRI) and lower heart rate (HR) at P0. During P1 OR showed higher cardiac index (CI), stroke volume index (SVI), and lower systemic vascular resistance index (SVRI) than OI. Both exhibited significant decreases in cerebral oxygenation and increases in cerebral deoxygenated hemoglobin, while OI showed decreases in cerebral oxygenated hemoglobin and peripheral oxygenation with increases in peripheral deoxygenated hemoglobin. During P2, OR maintained greater CI, systolic, mean, and diastolic pressure (SAP, MAP, DAP), with a shortened RRI compared to the OI group. Body weight and BMI showed high sensitivity (0.95), low specificity (0.33), PPV of 0.78, and OR of 0.92/0.61. For P1 delta SVI, sensitivity 0.91, specificity 0.44, PPV 0.79, and OR 0.8. For P2 delta SAP, sensitivity 0.95, specificity 0.67, PPV 0.87, and OR 0.9. Discussion: Maintaining OR during SHHOC relies upon baseline anthropometrics, increasing CI and SVI, minimising peripheral 02 utilisation and decreasing SVRI during hypoxia. During hypoxic LBNP, OR depends upon maintaining SAP, via CI increases. An increase in cerebral 02 consumption, coupled with increased peripheral 02 utilisation played a role in OI. Effective aerospace crew monitoring strategies can be implemented from these results .